What does the convenience yield curve tell us about the crude oil market? - Ron Alquist; Gregory H. Bauer; Antonio Díez de los Ríos (Bank of Canada, 2014)
Using the prices of crude oil futures contracts, we construct the term structure of crude oil convenience yields out to one-year maturity. The crude oil convenience yield can be interpreted as the interest rate, denominated in barrels of oil, for borrowing a single barrel of oil, and it measures the value of storing crude oil over the borrowing period. We show that the convenience yield curve is well explained by a level and a slope factor. Consistent with the theory of storage, convenience yields have predictive power over future crude oil inventories, production, global real economic activity and the price of oil.
Keywords: C53; G12; G13; Q43; 330; Asset pricing; International topics